Pengaruh Faktor Finansial, Capital Intensity, Inventory Intensity, dan Sales Growth terhadap Penghindaran Pajak Pada Saat Pandemi Covid-19 - Ni Luh Putu Saraswati Ardhanareswari; Murtanto (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to find out the influence of Financial Factors (Profitability, Leverage, and Firm Size), Capital Intensity, Inventory Intensity, and Sales Growth on the practice of Tax Avoidance. The results of the study prove that Profitability, Leverage, Firm Size, Capital Intensity, Inventory Intensity, and Sales Growth have a simultaneous effect on Tax Avoidance during the COVID-19 pandemic. Profitability, Firm Size, Inventory Intensity and Sales Growth have a negative effect on Tax Avoidance during the COVID-19 pandemi. Leverage and Capital Intensity have a positive effect on Tax Avoidance during the COVID-19 pandemic.